A NEEDS ANALYSIS ON THE DEVELOPMENT OF A MOBILE LEARNING (M-LEARNING) MODULE FOR MULTICULTURAL COUNSELLING - Daud, Nurul Ain Mohd; Jalal, Fauziah Hanim; Zain, Norzuhaidah Mohd; Noh, Noraini (The journal of contemporary issues in business and government, 2021)
Various studies in instructional strategies have been conducted to enhance multicultural counselling competency. However, there is a lack of pedagogical approach for technological aspects in multicultural counselling, particularly for mobile learning. This article highlights the development of the Multicultural Counselling Mobile learning (M-learning) module using the ADDIE model. It concentrates on the first stage of the module development, which involved the needs analysis study to construct the framework of the module. 86 respondents consisted of counselling students both undergraduate and postgraduate were involved in the study. The results of the study indicated the positive needs for mobile learning during teaching and learning. The discussion and implications of the study that helped in the planning and designing of the multicultural counselling competency module were discussed.